Effect of Microsporida Infection on the Esterases Activities in Agrotis segetum Caterpillars - Yefimenko, T.M.; Sundukov, O.V.; Issi, I.V. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2001)
Microsporida infection of Agrotis segetum Schiffermuller larvae causes numerous changes of separate fractions activities belonging to carboxylesterase isoenzyme complex. Such shifts are found to correlate with parasite development stages, activities of several fractions being increased early after Vairimorpha antheraeae incorporation up to the beginning of sporogony. During intensive sporogony and spore forming the enzyme activities are proved to decrease. Activities of multiple esterase molecular forms at different microsporidiosis stages may be correlated with cell pathology patterns and cell compartments damages taking part in the enzymes synthesis and transportation. These described changes may be also due to such Microsporidainduced pathological features as lipid metabolism and hormone balance impair followed by decreased reproductive function.